2019
DOI: 10.1097/sla.0000000000002754
|View full text |Cite
|
Sign up to set email alerts
|

IDO1 Expression Is Associated With Immune Tolerance and Poor Prognosis in Patients With Surgically Resected Esophageal Cancer

Abstract: IDO1 expression was associated with an unfavorable clinical outcome in esophageal cancer, supporting its role as a prognostic biomarker. Combining the IDO1 and CD8 statuses enabled further classification of the clinical outcomes of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 40 publications
4
65
0
Order By: Relevance
“…These data indicate that CD169 is more predictive of a better clinical prognosis and high anti‐cancer immune activity than IDO1. Although the literature contains many research articles related to IDO1 in cancer, including esophageal cancer, we believe the present report is the first to describe the expression of IDO1 in LySMs. IDO1 plays a critical role in promoting the immune evasion of cancer cells, and recent clinical trials have focused on the anti‐cancer effects of IDO1 inhibitors .…”
Section: Discussionmentioning
confidence: 79%
“…These data indicate that CD169 is more predictive of a better clinical prognosis and high anti‐cancer immune activity than IDO1. Although the literature contains many research articles related to IDO1 in cancer, including esophageal cancer, we believe the present report is the first to describe the expression of IDO1 in LySMs. IDO1 plays a critical role in promoting the immune evasion of cancer cells, and recent clinical trials have focused on the anti‐cancer effects of IDO1 inhibitors .…”
Section: Discussionmentioning
confidence: 79%
“…In a previous study, we reported that IDO1 expression was associated with an unfavorable clinical outcome in esophageal cancer . Other studies have also reported on the relationship between IDO1 expression and clinical outcomes in several types of cancer (Table ).…”
Section: Introductionmentioning
confidence: 67%
“…The relationship between IDO1 promoter hypomethylation, preoperative therapy, and patient outcomes needs to be confirmed in independent cohorts in the future. As another point of view, we analyzed the relationship between IDO1 promoter methylation levels, presence of CD8+ TIL, and prognosis because we reported the importance of the role of CD8 + TIL for esophageal cancer in previous studies . However, we found no direct association between CD8 + TIL status (Figure ), IDO1 promoter methylation, and OS (Figure ).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Immunosuppression checkpoint molecules, including PD‐L1/PD‐1, galectin‐9/TIM‐3, IDO1, LAG‐3, and CTLA4, can inhibit the activation of effector T lymphocytes, ultimately leading to tumor immune escape 13,35 . Blocking these immunocheckpoints has become critical in cancer cell immunotherapy in recent years.…”
Section: Discussionmentioning
confidence: 99%